A medium throughput device to study the effects of combinations of surface strains and fluid-flow shear stresses on cells. Issue 2 (7th November 2014) - Sinha, R.; Le Gac, S.; Verdonschot, N.; van den Berg, A.; Koopman, B.; Rouwkema, J.
Abstract : A device is reported to screen for the effects on cells of all combinations of five surface strains and five fluid-flow shear stresses, each with four replicates (total 100 units). Abstract : We report a medium throughput device to study the effects of combinations of two mechanical stimuli – surface strains and fluid flow shear stresses, on cells. The first generation prototype can screen combinations of five strain and five shear stress levels. Computational modeling and empirical measurements were used to determine the generated strains and flows. Uniform equibiaxial strains up to 20% and shear stresses up to 0.3 Pa can be generated. Compatibility of the device with cell culture and end point fixation, staining and imaging is shown using C2C12 mouse myoblast cells.